Geriatric psychiatry consultations in a Turkish university hospital - (:unkn) unknown (CAMBRIDGE UNIV PRESS, 2006)
Objectives: The size of the elderly population is growing rapidly in Turkey. We aimed to characterize geriatric psychiatry consultations to obtain the characteristic pattern of these patients for further interventions. Method: A retrospective chart review was undertaken for each patient. Results: One hundred and sixty-six patients with a mean age ( +/- S.D.) of 75.5 +/- 6.6 years were included in this study. Most referrals came from the Department of Internal Medicine (42.2%), with sleep problems (42.1%), depression (29.5%) and anxiety (28.3%) being the most common reasons for referral. Hypertension was the most frequent medical diagnosis (53.6%). The mean number ( +/- S.D.) of medications used by each patient was 4.4 +/- 2.0. The leading psychiatric diagnosis at the end of the assessment was adjustment disorder (31.3%). Conclusion: Turkish geriatric psychiatry consultation patients display similar characteristics to elderly patients from other western countries. The main difference comes from diagnosis of adjustment disorder, which may be related to hospital conditions and strong family ties in developing countries.
Keywords: consultation; geriatric psychiatry; elderly patients; adjustment disorder; general hospital; REFERRALS